IMPLEMENTASI GAME BASED LEARNING BERBANTUAN WORDWALL UNTUK MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Feby Arief Nugroho (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
Learning motivation in mathematics, especially fractions, remains a major challenge in elementary schools. Conventional teaching methods often make students less engaged and less motivated. This study aimed to examine the effect of Game Based Learning (GBL) assisted by Wordwall on students’ learning motivation. The research employed a quasi-experimental design with fifth-grade elementary students (n = 30) as participants. Motivation was measured using a Likert-scale questionnaire administered before and after the intervention. The results showed a significant increase in motivation, with pretest scores (M = 3.05, SD = 0.54) rising to posttest scores (M = 3.92, SD = 0.47). The paired sample t-test confirmed a significant improvement, t(29) = 7.86, p < 0.001, with a large effect size (d = 1.07). These findings suggest that Wordwall-based GBL effectively enhances motivation by engaging students through competition, instant feedback, and interactive activities